FACTORS AFFECTING INNOVATIVE WORK BEHAVIOR AMONG GENERATION Z OF STARTUP EMPLOYEES IN JAKARTA - Renata Alifia; Netania Emilisa; Zelda Dhiya Sulthoni; Anggita Agustia; Marsha Anita Muhadi (Universitas Nusa Cendana, 2025)
This study aims to examine the influence of Ethical Leadership and Proactive Personality on Innovative Work Behavior mediated by Work Engagement among Generation Z employees working in startup companies in Jakarta. A quantitative approach was applied through the distribution of questionnaires to 145 respondents using a purposive sampling method. The findings indicate that Ethical Leadership has a positive effect on Innovative Work Behavior, while Proactive Personality shows a negative direct influence. However, when mediated by Work Engagement, Proactive Personality exerts a positive effect on innovative behavior. These results suggest that proactive traits do not always directly result in innovation but can foster it when employees feel engaged and energized in their work. This study is limited to startups in Jakarta; therefore, future research is encouraged to broaden the geographical scope and incorporate additional variables to enhance understanding. Keywords: Ethical Leadership; Proactive Personality; Work Engagement; Innovative Work Behavior